Pengaruh Harga Dan Gaya Hidup Terhadap Keputusan Pembelian Pakaian Second Import Di Pasar Lemabang Palembang - Muhammad Qori Musyaffa; Iceu sri gustina; Syamsiar Zahrani (CV. ITTC INDONESIA, 2022)
This study aims to determine the effect of price and lifestyle on purchasing decisions for second imported clothing in the Lemabang market, Palembang. As for the problem in this study